Practical Issues of Health Data Processing According to General Data Protection Regulation - Januševičienė, Justina (Teisė, 2018)
The aim of the Member States of the European Union to find a balance among main freedoms, granted bythe European Union, technological progress, the interests of public security and the rights of individuals wasaccomplished with the adoption of Regulation (EU) 2016/679 of the European Parliament and of the council onthe protection of natural persons with regard to the processing of personal data and on the free movement of suchdata, and repealing Directive 95/46/EC (General Data Protection Regulation). It is believed that besides importantdata protection novelties, with are being introduced by General Data Protection Regulation, it’s provisions willhelp to achieve significant progress in international cooperation in the field of lifesciences and healthcare, whichwere restricted due to disparities among countries concerning personal health data for a while. The article focuseson questions whether General Data Protection Regulation brings in enough legal clarity and legal certainty intohealthcare, which is bound by the principle of subsidiarity. The article also deals with practical aspects of applicationof personal health data processing provisions of General data protection regulation.
Keywords: none